1999
DOI: 10.1093/ajcn/70.3.346
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in body weight and composition consequent to 20 wk of endurance training: the HERITAGE Family Study

Abstract: Background: Obesity is a major public health problem in the United States. The role of physical activity and formal exercise in controlling body weight has not been clearly determined. Objective: This study determined the magnitude of change in body weight and composition across sex, race, and age in response to 20 wk of endurance training. Design: Men and women (n = 557) of various ages (16-65 y) and 2 races (black and white) exercised on cycle ergometers 3 d/wk for a total of 60 exercise sessions starting at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
104
1
8

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(124 citation statements)
references
References 24 publications
11
104
1
8
Order By: Relevance
“…The lipid responses of similar TC levels, TG levels, and increased LDL-C levels among men over time are in contrast to the findings of Kraemer et al [13] who reported significant declines in TC levels, TG levels and LDL-C levels in D, E and DE plus Strength training (DES), while HDL-C remained unchanged from baseline to 12 weeks in men. Kraemer et al [13] reported the greatest reductions in TC and LDL-C levels in individuals who reduced body weight to the greatest extent.…”
Section: Serum Lipid Levelscontrasting
confidence: 98%
See 1 more Smart Citation
“…The lipid responses of similar TC levels, TG levels, and increased LDL-C levels among men over time are in contrast to the findings of Kraemer et al [13] who reported significant declines in TC levels, TG levels and LDL-C levels in D, E and DE plus Strength training (DES), while HDL-C remained unchanged from baseline to 12 weeks in men. Kraemer et al [13] reported the greatest reductions in TC and LDL-C levels in individuals who reduced body weight to the greatest extent.…”
Section: Serum Lipid Levelscontrasting
confidence: 98%
“…Similar to our results, Wilmore et al [13] observed a non-significant (0.9%) decrease in percent body fat over 20 weeks in 258 mildly obsess exercising men. Our findings are also in agreement with Kraemer et al [14] who reported that men in D and DE had significant decreases of 3.6% and 4.7% body fat, respectively, at the end of their 12-week study.…”
Section: Diet and Exercise On Body Compositionsupporting
confidence: 91%
“…Changes in physical activity, however, may lead to changes in body composition (increase in muscle mass, decrease in fat mass), and thus to a decreasing waist circumference, but stable body weight, and thus stable BMI. 4,5 The waist circumference is increasingly implemented in the field of epidemiology, clinical practice and prevention programs. Measuring waist circumference has been recommended as a useful tool for health promotion since the measurement of waist circumference is informative, easy, cheap and reliable.…”
Section: Tls Visscher and Jc Seidellmentioning
confidence: 99%
“…3 Changes in physical activity, for example, lead to changes in both lean (muscle) and fat mass, that were reflected by differences in waist circumference, while body weight remained stable. 4,5 Consequently, body weight may be less influenced by opposing trends in fat and lean mass, due to decreases in physical activity levels, than the waist circumference. The use of waist circumference is more and more being implemented for diagnosis of obesity and health promotion, but time trends in waist circumference levels are scarcely reported.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies reporting that men lose more visceral AT (VAT) than women are confounded by greater weight losses in men. 3,7,8 Nevertheless, studies that report a similar weight loss 1,2,9 still observe a greater reduction in VAT in men than in women. However, as reductions in AT are related to their initial values, 2,3 men may be expected to lose more VAT because they generally have more VAT than women.…”
Section: Introductionmentioning
confidence: 96%